Respuesta :

Answer:

y-intercept: (0,-4)

x-intercept: (-9,0)

Step-by-step explanation:

To find the y and x intercepts, simply plug in 0 for x or y in the equation.

y-intercept:

[tex]-\frac{4}{3} x - 3y = 12[/tex]

[tex]-\frac{4}{3} (0) - 3y = 12[/tex]

[tex]0 - 3y = 12[/tex]

[tex]-3y = 12[/tex]

[tex]y = -4[/tex]

(0,-4)

x-intercept

[tex]-\frac{4}{3} x - 3y = 12[/tex]

[tex]-\frac{4}{3} x - 3(0) = 12[/tex]

[tex]-\frac{4}{3} x - 0 = 12[/tex]

[tex]-\frac{4}{3} x = 12[/tex]

[tex]-4x = 36[/tex]

[tex]x = -9[/tex]

(-9,0)